2011
DOI: 10.1371/journal.pone.0024439
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Emetic Compounds on Chemotaxis in Dictyostelium Identifies a Non-Sentient Model for Bitter and Hot Tastant Research

Abstract: Novel chemical entities (NCEs) may be investigated for emetic liability in a range of unpleasant experiments involving retching, vomiting or conditioned taste aversion/food avoidance in sentient animals. We have used a range of compounds with known emetic /aversive properties to examine the possibility of using the social amoeba, Dictyostelium discoideum, for research into identifying and understanding emetic liability, and hence reduce adverse animal experimentation in this area. Twenty eight emetic or taste … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 107 publications
3
23
0
Order By: Relevance
“…To mimic salty taste, cells were exposed to increasing salt concentrations (potassium phosphate), from standard buffer conditions (24.2 mM potassium) up to a 3.3-fold increase (80 mM), and no gross change was observed in Dictyostelium cell shape following treatment. This is consistent with that reported by Robery et al (2011), where Dictyostelium does not respond to the salty tasting central nervous system depressant lithium chloride (Schiffman and Erickson, 1971) under equivalent conditions. To mimic sour taste (Da Conceicao Neta et al, 2007), cells were transferred to a buffer at pH 5 (from pH 6.3).…”
Section: Dictyostelium Cell Behavior Responds To Acute Application Ofsupporting
confidence: 92%
“…To mimic salty taste, cells were exposed to increasing salt concentrations (potassium phosphate), from standard buffer conditions (24.2 mM potassium) up to a 3.3-fold increase (80 mM), and no gross change was observed in Dictyostelium cell shape following treatment. This is consistent with that reported by Robery et al (2011), where Dictyostelium does not respond to the salty tasting central nervous system depressant lithium chloride (Schiffman and Erickson, 1971) under equivalent conditions. To mimic sour taste (Da Conceicao Neta et al, 2007), cells were transferred to a buffer at pH 5 (from pH 6.3).…”
Section: Dictyostelium Cell Behavior Responds To Acute Application Ofsupporting
confidence: 92%
“…Our previous study identified a strong and rapid effect of phenylthiourea on Dictyostelium cell movement (Robery et al, 2011), but a molecular mechanism for this effect was unclear. In order to identify this mechanism, we first established conditions necessary for a mutant screen, based upon resistance to a block in growth caused by phenylthiourea in shaking suspension.…”
Section: Identification Of a Phenylthiourea Receptor In Dictyosteliummentioning
confidence: 98%
“…We have previously reported a potent and rapid onset block in Dictyostelium cell behaviour (shape and movement) during chemotaxis for several bitter tastants, including phenylthiourea (Robery et al, 2011). This response was unexpected because Dictyostelium does not contain genes encoding homologues to T2R proteins associated with phenylthiourea detection.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Chemotaxis assays were performed as described previously (Robery et al, 2011). In brief, cells were pulsed at a density of 1.7610 6 cells/ml with 30 nM cAMP at 6 minute intervals for 5 hours before plating on coverslips.…”
Section: Cell Movement and Image Acquisitionmentioning
confidence: 99%